PECULIARITIES OF DEFORMATION BEHAVIOR OF POLYMERIC MIXTURES OF POLYVINYL CHLORIDE WITH POLYETHYLENE IN THE PRESENCE OF COMPATIBILIZERS - Khakberdiev Elshod Olmosovich , Berdinazarov Qodirbek Nuridin ugli , Sadikov Shukhrat Gafurovich , Ashurov Nigmat Rustamovich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this work, we investigated the features of deformation of polymer mixtures PVC / PE, obtained in the presence of two types of compatibilizers, a comparative assessment of the elastic - strength characteristics of the mixtures versus and variations in the intensity of mixing of components in the melt is carried out. The effect of plasticization of PVC with dioctyl phthalate was found with an increase in the stirring speed, expressed by a decrease in the modulus of elasticity and stress at the yield point. For mixtures with a PVC matrix in the absence of a compatibilizer, an increase in the PE content leads to a drop in stress at the yield point and elongation at break; for equal mixture compositions with intense mixing, the deformation curves show a combination of the yield zone and orientational ordering. The presence of a compatibilizer (5-15% by weight) in the composition leads to an increase in interfacial adhesion, which is shown at low contents of polyethylene in the mixture - the values of Young’s modulus in the presence of compatibilizers are much higher than the additive curve.